2021
DOI: 10.1002/brb3.1988
|View full text |Cite
|
Sign up to set email alerts
|

The effects of voluntary complex and regular wheel running exercises on the levels of 8‐oxoguanine DNA glycosylase, semaphorin 3B, H2O2, and apoptosis in the hippocampus of diabetic rats

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…In this regard, previous studies have confirmed that exercise training, especially aerobic training raises cell proliferation in the dentate gyrus [ 14 ] and hippocampal plasticity [ 15 ], up-regulates brain-derived neurotrophic factor (BDNF) and neuron growth factor (NGF) and down-regulates the genes associated with oxidative stress [ 12 , 16 ]. Most studies have used running training [ 17 19 ] to assess the effect of exercise training on diabetes-induced neurodegenerative diseases, and the protective or offensive role of swimming training in memory performance is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, previous studies have confirmed that exercise training, especially aerobic training raises cell proliferation in the dentate gyrus [ 14 ] and hippocampal plasticity [ 15 ], up-regulates brain-derived neurotrophic factor (BDNF) and neuron growth factor (NGF) and down-regulates the genes associated with oxidative stress [ 12 , 16 ]. Most studies have used running training [ 17 19 ] to assess the effect of exercise training on diabetes-induced neurodegenerative diseases, and the protective or offensive role of swimming training in memory performance is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggests that astrocytes are very likely the main cell type in the brain that are affected by these metabolic alterations that may lead to impaired glutamine synthesis, loss of synaptic proteins and eventually synaptic maladaptation and brain dysfunction. Previous studies conducted in young animals with metabolic disturbances showed that physical activity can improve brain function by reducing oxidative stress and lipid peroxidation 68 71 , modulating immune responses and reducing neuroinflammation 68 , 69 , 72 75 , and improving insulin signaling and glucose utilization 68 , 75 – 79 . Our study also showed that two months of voluntary wheel running significantly improves learning and memory.…”
Section: Discussionmentioning
confidence: 99%